2013
DOI: 10.1182/blood-2013-06-507319
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of minimal residual disease in bone marrow predicts outcome in follicular lymphomas treated with a rituximab-intensive program

Abstract: Key Points• PCR negativity is a strong outcome predictor after rituximab-intensive immunochemotherapy at multiple posttreatment times.• PCR is predictive even when maintenance is delivered, and accumulation of PCR-negative results further reduces the likelihood of relapse.We assessed the prognostic value of minimal residual disease (MRD) within the ML17638 phase 3 trial from the Fondazione Italiana Linfomi, investigating the role of rituximab maintenance in elderly follicular lymphoma (FL) patients after a bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 50 publications
(66 reference statements)
3
58
1
Order By: Relevance
“…However, a recent study from our group in old patients receiving R-FND followed by a brief consolidation with rituximab and a random between rituximab maintenance or observation showed power that MRD still retained an excellent prognostic discrimination among patients receiving rituximab maintenance (15). Moreover, our data suggest that a preemptive strategy similar to that used by the Nordic group in mantle cell lymphoma might appear of interest for future studies in follicular lymphoma, as also shown by the retrospective experience from our group (28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a recent study from our group in old patients receiving R-FND followed by a brief consolidation with rituximab and a random between rituximab maintenance or observation showed power that MRD still retained an excellent prognostic discrimination among patients receiving rituximab maintenance (15). Moreover, our data suggest that a preemptive strategy similar to that used by the Nordic group in mantle cell lymphoma might appear of interest for future studies in follicular lymphoma, as also shown by the retrospective experience from our group (28).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that levels of BCL2/IGH <1 Â 10 À3 did not improve quality of response (14), whereas others showed that cases with low molecular tumor burden at diagnosis achieved CR more frequently than those with high molecular tumor burden (15). In our study, we demonstrated that cases displaying values <1 Â 10 À4 showed a clear advantage in terms of PFS (3-year PFS 80% vs. 59% for cases with higher molecular tumor burden; P ¼ 0.015) and ORR (76.6% vs. 38.9%; P ¼ 0.006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate our molecular data, 54 samples of peripheral blood, bone marrow and apheresis were tested in the Laboratory of Molecular Biology in Turin belonging to the EURO-MRD consortium [9]. A qualitative PCR was conducted in blinded fashion for bcl-2 (MBR and mcr).…”
Section: Molecular Responsementioning
confidence: 99%